(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the current compliance status of healthcare workers with the surgical safety checklist at Saigon General Hospital in 2025. Subject and methods: A descriptive cross-sectional study was conducted through direct observation of health care worker compliance with the surgical safety checklist, including scrub nurses, anesthesiologists and anesthesia nurses, and surgeons. A total of 137 surgical procedures were observed from April to July 2025. Results: The overall compliance rate was 70.8%. Compliance rates by phase were 78.1% before anesthesia induction, 77.4% before skin incision, and 83.2% before the patient left the operating room. Among the professional groups, scrub nurses demonstrated the highest compliance (78.1%), followed by surgeons (71.5%) and anesthesiologists, anesthesia nurses (70.8%). Conclusion: The rate of compliance with the surgical safety checklist at the hospital is not high, therefore, the hospital needs to develop a clear penalty mechanism, increase the frequency of assessment and supervision to raise the compliance awareness of staff as well as measures to improve equipment to increase the rate of compliance with the surgical safety checklist.